2016
DOI: 10.1093/jac/dkw054
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in antibiotic prescribing in the community: a systematic review and meta-analysis

Abstract: This meta-analysis shows that women in the 16 to 54 years age group receive a significantly higher number of prescriptions of cephalosporins and macrolides in primary care than men do. Prospective studies are needed to address reasons for gender inequality in prescription and to determine whether a difference in adverse events, including resistance development, also occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
85
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 37 publications
15
85
5
2
Order By: Relevance
“…If men are more susceptible to infections than women, we would expect to find that the use of anti-infective medications increases more after spousal loss among men than among women. In light of previous research findings indicating that levels of all-cause medication use 10 and antibiotic use, particularly for RTIs and UTIs, are higher among women than among men, 29 we would expect to observe higher levels of anti-infective medication use among women than among men both before and after widowhood.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…If men are more susceptible to infections than women, we would expect to find that the use of anti-infective medications increases more after spousal loss among men than among women. In light of previous research findings indicating that levels of all-cause medication use 10 and antibiotic use, particularly for RTIs and UTIs, are higher among women than among men, 29 we would expect to observe higher levels of anti-infective medication use among women than among men both before and after widowhood.…”
Section: Introductionmentioning
confidence: 72%
“…29 Previous studies conducted in Denmark have shown that women tend to take more all-cause medications and visit general practitioners more frequently than men. 10 These patterns may be partially explained by a greater reluctance among men than among women to seek medical advice in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic use also varies by individual factors, such as knowledge [17], gender [18], education [17,19], age [20], trust in institutions [6] and interpersonal trust [6,21].…”
Section: Previous Researchmentioning
confidence: 99%
“…The first is age, since older patients have been found to consume more antibiotics [20], while this group also tends to report higher levels of interpersonal trust [56,57]. A second aspect is that gender has been related to cooperation in some collective action dilemmas [58], while women consume more antibiotics [18]. Furthermore, subjective health is linked to higher levels of interpersonal trust [59], and positive health decisions [60], while people with higher stated well-being are more willing to wait to consume antibiotics [6].…”
Section: Design Of the Cross-section Survey Studymentioning
confidence: 99%